Enhancing systemic lupus erythematosus care and outcomes through innovative interventions by the rheumatology initiative (tRi) in Ghana - Dey, Dzifa; Bobade, Rosetta; Katso, Bright; Issaka, Saudatu; Charis, Angela; Can Tamakloe, Abdul Aziz; Narh, Padiki (Frontiers in Lupus, 2024)
Rheumatic diseases like Lupus are complex autoimmune conditions with diverse manifestations presenting challenges for diagnosis and management globally. Access to rheumatology expertise and education varies significantly across different regions, particularly in low-resource settings. These diseases pose significant challenges to healthcare systems worldwide, including developing countries like Ghana. To address these resource gaps and optimise patient care, innovative solutions must be pursued. The Rheumatology Initiative (tRi) in Ghana aims to improve the understanding, diagnosis, and management of rheumatic conditions through educational activities, research projects, and targeted interventions. This article provides an overview of tRi's initiatives to bridge the rheumatology resource gap, focusing on educational efforts, project targets, and their outcomes, with specific attention to systemic lupus erythematosus (SLE) in the Ghanaian context. We highlight the progress made by tRi and underscore the importance of continued collaboration and support for rheumatology initiatives in resource-limited settings to improve management and awareness.